Políticas Públicas de Resíduos Sólidos e a Coleta Seletiva em Regente Feijó - SP - Martins, Francielle Garcia [UNESP] (Universidade Estadual Paulista (Unesp), 2011)
This research was mainly focused on public policy analysis of solid waste, and the National Policy and State Solid Waste, as well as determining the performance of the Blue Green Municipality strategic project in relation to the management of municipal solid waste in Regente Feijó, São Paulo. The objective of this research was to analysis of the consequences of the deployment project of selective collection and integration of recyclable material collectors in an association of collectors, called the Association of Recyclable Material Collectors Rock, held in the city from the year 2008, with effective implementation in 2010. We analyzed the actions of the municipal government since the implementation of selective collection, to the development of the Association. The methodology used was literature concerning the issue; routine field surveys to monitor the activities in the landfill and association of collectors, collecting data from questionnaires appropriate to the research topic. We sought to examine old and new forms of urban solid waste management, the evolution of the historical process of this issue in the city and its social and environmental impacts, and the collectors the main social actors in this process. The complexity that addresses this issue was dealt with in this dynamic study, analyzing all parts involved

A presente pesquisa teve como foco principal a análise das políticas públicas de resíduos sólidos, sendo a Política Nacional e Estadual de Resíduos Sólidos, bem como a atuação do projeto estratégico Município Verde Azul no que tange ao gerenciamento de resíduos sólidos urbanos em Regente Feijó, São Paulo. Objetivou-se com esse trabalho a análise dos desdobramentos do projeto de implantação da coleta seletiva e inserção dos catadores de materiais recicláveis numa associação de catadores, denominada “Associação de Catadores de Materiais Recicláveis Rocha”, realizada no município a partir do ano de 2008, com efetiva implantação no ano de 2010. Analisou-se a as ações do poder público municipal desde a implantação da coleta seletiva, até o desenvolvimento da Associação. Como metodologia, utilizou-se levantamento bibliográfico referente ao tema; trabalhos de campo rotineiros, para acompanhamento das atividades no aterro controlado e associação de catadores; levantamento de dados a partir de questionários adequados ao tema pesquisado. Buscou-se analisar as antigas e atuais formas do gerenciamento de resíduos sólidos urbanos, a evolução do processo histórico dessa questão no município e seus impactos socioambientais, sendo os catadores os principais atores sociais nesse processo. A complexidade que essa questão aborda, foi tratada de forma dinâmica nesse trabalho, analisando todas as partes envolvidas
Keywords: Geografia; Politicas publicas - Regente Feijó (SP); Resíduos sólidos; Catadores de lixo - Regente Feijó (SP); Impacto ambiental; Projeto “Município VerdeAzul”